Theoretical explanation and regulation method for the edge effect in the sintered joints of metal nanoparticles - Guannan Yang; Zebo Li; Zhihao Zhang; Junyi Lu; Yu Zhang; Guanghan Huang; Tianshuo Zhao; Chengqiang Cui (Journal of Materials Research and Technology, 2025)
A theoretical model is proposed to explain the edge effect observed in sintered metal nanoparticle joints, which are characterized by a relatively loose and porous structure near the joint edges. By modeling the metal particle slurry as a granular system that follows the Mohr-Coulomb criterion, an exponential stress distribution is predicted, with high pressure at the center and low pressure at the edges, which reasonably explains the origin of the edge effect. With this understanding, a geometrically constrained sintering process is further proposed to mitigate the edge effect by using a pre-cured resin sealing layer around the chip edges to suppress the lateral flow of the metal nanoparticle slurry. Experimental results show that the constrained sintering process leads to the formation of a dense and uniform sintering structure in the sintered joint that has a 90 % enhancement in overall shear strength.